2015
DOI: 10.5194/soil-1-475-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fresh and aged chars from pyrolysis and hydrothermal carbonization on nutrient sorption in agricultural soils

Abstract: Abstract. Leaching of nutrients from agricultural soils causes major environmental problems that may be reduced with amendments of chars derived from pyrolysis (pyrochars) or hydrothermal carbonization (hydrochars). Chars are characterized by a high adsorption capacity -i.e. they may retain nutrients such as nitrate and ammonium. However, the physicochemical properties of the chars and hence their sorption capacity likely depend on feedstock and the production process. We investigated the nutrient retention ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 51 publications
(91 reference statements)
6
27
0
Order By: Relevance
“…Ventura, Sorrenti, Panzacchi, George, and Tonon (2013) observed a reduction in NO 3 -N leaching only in the second year after biochar application, suggesting an increase in biochar sorption properties over time, possibly due to the oxidation and interaction of biochar and soil particles and an increase in the adsorbing surface due to particle fragmentation with aging (Hagemann et al, 2017;Singh, Hatton, Singh, Cowie, & Kathuria, 2010). In contrast, Gronwald, Don, Tiemeyer, and Helfrich (2015) observed that the adsorption capacity of biochar decreased by 60-80% to less or observed no NO 3 /NH 4 -N adsorption after 7 mo of aging in the field compared with the fresh char. A similar trend of decreasing adsorption capacity with biochar from beetroot chips was reported from a laboratory study on loam soil (Bargmann, Martens, Rillig, Kruse, & Kücke, 2014).…”
Section: Nitrate Leachingmentioning
confidence: 99%
“…Ventura, Sorrenti, Panzacchi, George, and Tonon (2013) observed a reduction in NO 3 -N leaching only in the second year after biochar application, suggesting an increase in biochar sorption properties over time, possibly due to the oxidation and interaction of biochar and soil particles and an increase in the adsorbing surface due to particle fragmentation with aging (Hagemann et al, 2017;Singh, Hatton, Singh, Cowie, & Kathuria, 2010). In contrast, Gronwald, Don, Tiemeyer, and Helfrich (2015) observed that the adsorption capacity of biochar decreased by 60-80% to less or observed no NO 3 /NH 4 -N adsorption after 7 mo of aging in the field compared with the fresh char. A similar trend of decreasing adsorption capacity with biochar from beetroot chips was reported from a laboratory study on loam soil (Bargmann, Martens, Rillig, Kruse, & Kücke, 2014).…”
Section: Nitrate Leachingmentioning
confidence: 99%
“…Agriculture is one of the main causes of the desertification of the land, and this is partially due to the exhaustion of the soil nutrients (Kraaijvanger & Veldkamp, 2015;Lü et al, 2016;Lucas-Borja et al, 2016;Udeigwe et al, 2016). There is a need to restore the degraded lands (Chen et al, 2016;Costantini et al, 2016), and the recovery of the nutrients is a key strategy (Gronwald et al, 2015;Silvestri et al, 2016;Wang et al, 2016a). Potassium (K) is an essential element for higher plants; it plays a particularly crucial role in a number of physiological processes vital to growth, yield, quality and stress resistance of all crops (Pettigrew, 2008;Römheld & Kirkby, 2010;Zörb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, derivatives of organic carbon such as composts (Srinivasarao et al, 2014b;Mahmoud & El-Kader, 2015;Montiel-Rozas et al, 2016) and biochar have been considered to be a productive solution to various environmental problems, including soil that has been contaminated with potentially toxic elements (Sohi, 2012;Paz-Ferreiro et al, 2014). Biochar is a high-carbon and fine-grained residue which is produced from organic carbon under thermal decomposition in the absence of oxygen (Lehmann, 2009;Gronwald et al, 2015). Biochar as a soil amendment is used to improve soil quality over both the long and short term (Khaledian et al, 2013;Krause et al, 2016).…”
Section: Introductionmentioning
confidence: 99%